2010
DOI: 10.1111/j.1365-2710.2009.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Saffron in the treatment of patients with mild to moderate Alzheimer’s disease: a 16-week, randomized and placebo-controlled trial

Abstract: This double-blind, placebo-controlled study suggests that at least in the short-term, saffron is both safe and effective in mild to moderate AD. Larger confirmatory randomized controlled trials are called for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 33 publications
(66 reference statements)
6
125
1
3
Order By: Relevance
“…Τhe antioxidant properties of extract of C. sativus stigmas and its effect on Aβ1-40 fibrillogenesis were evaluated in double-blind, placebo-controlled study in 46 patients with Alzheimer's disease. [54] Patients group that received 15 mg of saffron extract twice daily for 16 weeks had better outcome on cognitive functions than the placebo group. In a second study of the same research group, [33] the same saffron extract dose was administered to 54 adults with mild to moderate Alzheimer's disease, age older than 55 years, in comparison with standard administration of 10 mg/day of donepezil, for 22 weeks.…”
Section: Eirini Christodoulou Et Almentioning
confidence: 88%
See 2 more Smart Citations
“…Τhe antioxidant properties of extract of C. sativus stigmas and its effect on Aβ1-40 fibrillogenesis were evaluated in double-blind, placebo-controlled study in 46 patients with Alzheimer's disease. [54] Patients group that received 15 mg of saffron extract twice daily for 16 weeks had better outcome on cognitive functions than the placebo group. In a second study of the same research group, [33] the same saffron extract dose was administered to 54 adults with mild to moderate Alzheimer's disease, age older than 55 years, in comparison with standard administration of 10 mg/day of donepezil, for 22 weeks.…”
Section: Eirini Christodoulou Et Almentioning
confidence: 88%
“…Alzheimer's disease Clinical study: 16-week, double-blind study, randomized, placebocontrolled study. [54] 40 patients with mild to moderate Alzheimer's disease randomized to receive: capsule saffron (15 mg twice per day) or (two capsules placebo per day).…”
Section: Anxiety and Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…Akhondzadeh et al in a double-blind, placebocontrolled study suggests that at least in the short-term, saffron (30 mg/day for 16 weeks) is both safe and effective in mild to moderate Alzheimer's disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Crocetin has been reported to inhibit Aβ fibrillization and stabilize Aβ oligomers [13]. We recently reported that crocetin prevents retinal damage induced by H 2 O 2 , tunicamycin, and N-methyl-Daspartate (NMDA) [14,15]; saffron extracts have been reported to be effective on memory deficit on mild AD patient [16,17]. However, there was no report on protective effects of crocetin in hippocampal neuronal cells having been examined.…”
Section: Introductionmentioning
confidence: 96%